2006
DOI: 10.1088/0963-0252/15/2/s12
|View full text |Cite
|
Sign up to set email alerts
|

Problems in lightning physics—the role of polarity asymmetry

Abstract: Many outstanding problems in lightning physics are linked with a difference in macroscopic behaviour between positive and negative polarity. Such differences are referred to broadly as 'polarity asymmetry'. As specific examples, the positive and negative ends of lightning propagate at different speeds, with different degrees of steadiness, and with different radiated electromagnetic energy. Positive and negative flashes to ground transfer their charge in markedly different ways-negative flashes with multiple d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
148
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 106 publications
8
148
0
1
Order By: Relevance
“…If we assume that a leader could only propagate if it has active negative and positive ends, then the recoil events themselves likely are small bidirectional systems: The original positive leader is their positive end, their negative end crawls back along the previously formed channel system. This was speculated by Williams [2006] and appears confirmed by high-speed camera recordings of Warner et al [2012].…”
Section: Summary Of Observationsmentioning
confidence: 55%
See 1 more Smart Citation
“…If we assume that a leader could only propagate if it has active negative and positive ends, then the recoil events themselves likely are small bidirectional systems: The original positive leader is their positive end, their negative end crawls back along the previously formed channel system. This was speculated by Williams [2006] and appears confirmed by high-speed camera recordings of Warner et al [2012].…”
Section: Summary Of Observationsmentioning
confidence: 55%
“…Williams [2006] offers an extensive review of the observed characteristics of negative and positive polarity leaders and notes their asymmetry at different scales. Williams and Heckman [2012] proposed that the zero induced charge point remains centered on the conductor, implying that it shifts from the flash origin into the direction of the positive charge region, using a linear potential profile.…”
Section: Introductionmentioning
confidence: 99%
“…However, negative streamers are clearly present in many natural phenomena of atmospheric electricity like lightning, sprite discharges etc. [1,3,4,5]. Furthermore, modern high voltage supplies easily create negative streamers [2,6,7], and they are very promising for disinfection applications [8] if electrical matching problems can be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Streamers are used in industrial applications such as lighting [3,4] or gas and water purification [5,6], and they occur in natural processes as well such as lightning [7,8,9] or transient luminous events in the upper atmosphere [10]. Therefore accurate modeling and simulation of streamers is of high interest.…”
Section: Introductionmentioning
confidence: 99%